Building Employee Competence Through Human Resource Training and Development at Carsurin Banjarbaru Company - Azzahraty; Ambarwati, Riris; Permana, Yudi; Firdaus (International Journal of Economics (IJEC), 2025)
Employee training is an important strategy for improving a company’s human resource competency. This study aimed to analyze the effect of training on employee competency by considering control variables such as work motivation, experience, and education level. The research design was a quantitative explanatory survey. The population in this study was  42 employees of PT Carsurin Banjarbaru Branch, using a proportionate stratified random sampling technique. Data analysis was performed using descriptive statistics, classical assumption tests (normality and multicollinearity), and multiple linear regression, with a significance level of α = 0.05. The results showed that training had a positive and significant effect on employee competency (p < 0.05, R² = 0.65) even after controlling for motivation, experience, and education variables. No multicollinearity problems were found in the model (VIF < 10), and the residual data were normally distributed. These findings indicate that well-designed training programs play an important role in improving employee knowledge, skills, and work attitudes. Practically, these results suggest that companies should place more emphasis on developing relevant training materials, improving instructor quality, and using applicable training methods